CIRCADIAN CLOCK-ASSOCIATED 1 Inhibits Leaf Senescence in Arabidopsis - Song, Yi; Jiang, Yupei; Kuai, Benke; Li, Lin (Frontiers in Plant Science, 2018)
Leaf senescence is an integral part of plant development, and the timing and progressing rate of senescence could substantially affect the yield and quality of crops. It has been known that a circadian rhythm synchronized with external environmental cues is critical for the optimal coordination of various physiological and metabolic processes. However, the reciprocal interactions between the circadian clock and leaf senescence in plants remain unknown. Here, through measuring the physiological and molecular senescence related markers of several circadian components mutants, we found that CIRCADIAN CLOCK-ASSOCIATED 1 inhibits leaf senescence. Further molecular and genetic studies revealed that CCA1 directly activates GLK2 and suppresses ORE1 expression to counteract leaf senescence. As plants age, the expression and periodic amplitude of CCA1 declines and thus weakens the inhibition of senescence. Our findings reveal an age-dependent circadian clock component of the process of leaf senescence.